IMPLEMENTASI FAILOVER VPN KANTOR PUSAT DAN CABANG MENGGUNAKAN TEKNOLOGI SDWAN DENGAN STRATEGI BEST QUALITY - Sahrul Hidayat; Yuma Akbar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Head office and branch VPN networks are used to connect the head office with branches spread across geographically separated areas. However, network security and availability can be affected by various factors, such as internet connection failures, excessive bandwidth usage, and other disturbances. To overcome this, researchers provide a solution for implementing Failover VPN at the head office and branches using SDWAN technology. With SDWAN, companies can choose a connection path that is more reliable and has a higher speed, thereby optimizing bandwidth usage and improving network availability. In this study, researchers tried to simulate Headquarters and Branch Office VPN Failover Using SDWAN Technology with the Best Quality Strategy at PNETLab. This study uses 2 connections, namely internet connection and MPLS. MPLS is Primary and the internet as Backup. The test is carried out using three schemes, scheme 1 when in normal conditions, scheme 2 when the packet loss on the MPLS link increases then traffic is taken over by the internet connection, and scheme 3 when the packet loss on the MPLS link returns to normal.